2012
DOI: 10.1167/iovs.12-10003
|View full text |Cite
|
Sign up to set email alerts
|

Visual Performance with Wave Aberration Correction after Penetrating, Deep Anterior Lamellar, or Endothelial Keratoplasty

Abstract: PK eyes had better logMAR VA than that of DSAEK eyes with LOA correction, whereas DALK eyes performed intermediate between the two. When full correction was applied, the same trend persisted. The findings suggest that factors other than aberration contribute to decrements in VA with DSAEK compared with PK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…Therefore, comparisons between the study groups cannot be accurately made, although the authors suggested that the discrepancy in visual outcomes could be partially attributed to light scatter caused by corneal haze. 91 This hypothesis was supported by Maier et al, who compared 10 patients who had received DMEK in one eye and DSAEK in the other. 75 Both BCVA and contrast sensitivity were significantly better in the DMEK eyes, but this was not explained by any significant difference in LOAs or HOAs between the two techniques, thus implicating other factors.…”
Section: High Order Aberrations and Light Scattermentioning
confidence: 85%
See 4 more Smart Citations
“…Therefore, comparisons between the study groups cannot be accurately made, although the authors suggested that the discrepancy in visual outcomes could be partially attributed to light scatter caused by corneal haze. 91 This hypothesis was supported by Maier et al, who compared 10 patients who had received DMEK in one eye and DSAEK in the other. 75 Both BCVA and contrast sensitivity were significantly better in the DMEK eyes, but this was not explained by any significant difference in LOAs or HOAs between the two techniques, thus implicating other factors.…”
Section: High Order Aberrations and Light Scattermentioning
confidence: 85%
“…These include abnormal diffraction in the posterior graft, anterior host cornea, and the interface; high order aberrations (HOAs) related to surface and interface irregularity; and light scatter from corneal haze. 84,91,137 Patients with high contrast visual acuity of 20/20 or better may complain of poor visual quality secondary to phenomena such as glare and poor contrast sensitivity that do not always correlate with visual acuity. A full assessment of visual quality therefore requires testing of these visual functions, not just high contrast acuity.…”
Section: Visual Acuity Versus Visual Qualitymentioning
confidence: 99%
See 3 more Smart Citations